HIGH GRADE GLIOMA - Salokhiddinov Khabibullo Adhamjon ugli (European Science Publishing, 2025)
High-grade gliomas (HGGs) are a category of aggressive brain tumors with poor prognosis and limited treatment options. These tumors are characterized by their rapid growth, invasive nature, and resistance to conventional therapies. This article explores the current understanding of high-grade gliomas, including their pathophysiology, diagnosis, and treatment options. The review highlights the challenges in managing these tumors, the latest research findings, and potential future therapeutic strategies. Early diagnosis and novel therapeutic approaches, such as immunotherapy and personalized medicine, are also discussed as promising avenues for improving patient outcomes.
Keywords: High-grade glioma, glioblastoma, brain tumor, treatment, immunotherapy, personalized medicine, prognosis, biomarkers.